2023
DOI: 10.3390/jpm13050813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thyroid Cancer Treatment on Renal Function: A Relevant Issue to Be Addressed

Abstract: Thyroid cancers require complex and heterogeneous therapies with different impacts on renal function. In our systematic literature review, we analyzed several aspects: renal function assessment, the impact of radiotherapy and thyroid surgery on kidney functioning, and mechanisms of nephrotoxicity of different chemotherapy, targeted and immunologic drugs. Our study revealed that the renal impact of thyroid cancer therapy can be a limiting factor in all radiotherapy, surgery, and pharmacological approaches. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
0
0
Order By: Relevance
“…Fatigue and insomnia are two common long-term complications of thyroidectomy, and from our clinical routine of post-surgery attendant, some patients complained of post-operative fatigue and insomnia. Previous publications also reported kidney injury after thyroidectomy (37) and some metabolites were associated with cancer-related renal diseases (Table S6). Our findings showed that metabolites associated with fatigue (Figure 5A) were enriched into set of cysteine and methionine metabolism, with changes of 5-methylthioadenosine (MTA) and cysteine.…”
Section: Discussionmentioning
confidence: 80%
“…Fatigue and insomnia are two common long-term complications of thyroidectomy, and from our clinical routine of post-surgery attendant, some patients complained of post-operative fatigue and insomnia. Previous publications also reported kidney injury after thyroidectomy (37) and some metabolites were associated with cancer-related renal diseases (Table S6). Our findings showed that metabolites associated with fatigue (Figure 5A) were enriched into set of cysteine and methionine metabolism, with changes of 5-methylthioadenosine (MTA) and cysteine.…”
Section: Discussionmentioning
confidence: 80%